Spatial distribution of soil nitrogen phosphorus and potassium in black pepper cultivation in Sarawak, Malaysia - Abd Hamid @ Ghazali, Izzah (2018)
Black pepper in Sarawak is cultivated on hilly topography due to natural land formation which provide good water drainage. Nitrogen, phosphorus and potassium are mostly insufficient due to nutrients loss subsequent to leaching and surface runoff. A study combining the use of global positioning system (GPS) and geographic information system (GIS) was conducted in selected black pepper farm in Bintulu (NL and SM), Kapit (SA), Sri Aman (AM), Serian (SR) and Kuching (BA and SK), Sarawak with the intention to determine soil physicochemical, conceivable correlation and spatial distribution using ordinary Kriging interpolation method to scrutinise distribution of N, P and K in various topography and farm background. A total of 416 soil samples were analysed for organic carbon, soil texture, soil pH, total N, available P, K, Ca, Mg, Fe and Mn. It was found that all soils was dominant rocks of sandstone, shales, limestone and alluvium. Generally, OC (2.02 to 5.04%) increased from Kuching <Serian <Sri Aman <Kapit <Bintulu and the soil pH was considered to be extremely acid to very strongly acidic. The availability of Fe was higher in NL (6 X 10-2 to 3.4 X 10-1 g kg-1) when compared to six other farms. Ultimately, P (5 X 10-6 to 7 X 10-3 g kg-1) and K (3 X 10-2 to 1.1 X 10-1 g kg-1) availability were been found to be strongly affected by high Fe concentration as compared to N. Lack of P explained by the formation of Fe-P complexes while K could have been leached out and replaced by Fe3+ which is very common in many tropical soils. The relationship between soil properties showed a positive correlation between OC with Mn, N, P, K, Ca and Mg which indicated an upsurge in the soil properties. Presence of OC as a soluble chelating agent, retained nutrients in the soil system. The negative correlation between soil pH against Fe, P, K, Ca and Mg have caused leaching out of cations in following order K >Ca >Mg and replaced by Fe. The spatial correlation of N, P and K for seven farms were modelled through isotropic which indicated linear, spherical, exponential and Gaussian. This prediction was acceptable with lower value obtained through leave-one-out validation method that provides mean error (-0.0329 to 0.0052) close to zero and unbiased prediction. Ordinary Kriging interpolation mapped showed the distribution of N to be affected by topography, soil texture and OC. As for P and K, the distribution was affected by Fe fixation, fertilizer application technique and soil acidity. Availability of N, P and K in those farms can be improved through annual lime application, mulching and growing of cover crops around black pepper poles which are seldom practised due to production cost and low awareness among farmers. It can be concluded that the availability of N, P and K in the research areas were affected by various factors such as soil mineralogy, topography, improper soil and land management (i.e. bare soil, absence of terracing and insufficient application of lime).